Development of Differentiated Learning Model Based on Gamification for Elementary School Children - Fajarianto, Otto; Wulandari, Dwi; Setiyowati, Arbin Janu; Ayunin, Qurrota; Maryam, Sinta Dewi; Ayunin, Salsabella Qurrota; Ismail, Affero (IJESS International Journal of Education and Social Science, 2025)
Differentiated learning is an effort to adapt the learning process to the learning needs of each student. Education in Indonesia, through the independent curriculum, is starting to introduce a lot of student-oriented learning. So there needs to be an appropriate learning approach that can be applied to learning activities. So the aim of this research is to evaluate previous scientific research articles related to differentiated learning in elementary schools (SD). In order to examine the usefulness of the differentiated learning approach in elementary schools (SD). In this article, the research method used is a literature review. The research data used are articles published within the last 5 years, namely between 2019 and 2023. As well as at the elementary school (SD) education level. This research stage was carried out by searching the literature with the keyword "Differentiated Learning" with findings of 6,280 articles. Then data selection was based on criteria according to the year of publication and research topic, namely differentiated learning at elementary school (SD) level, where 16 articles were obtained. Next, analyze the data as well as interpret and write the results and conclusions of the data analysis. Based on the results of the literature review analysis, it can be concluded that teachers can implement differentiated learning in the classroom well by providing a good understanding of differentiated learning. Then the benefit of implementing differentiated learning is that it can facilitate the diversity of students' learning needs based on learning styles. The application of differentiated learning has the potential to improve students' academic achievement and interest in learning. The application of differentiated learning in the classroom can also improve 21st century skills and support the implementation of independent learning.